Shaykh Nawawi al-Bantani's Intellectual Contribution to Ḥadīth Studies in Indonesia - Anisa Fitriyani; Arbi Fauzan; Azis Arifin (Sufiya Journal of Islamic Studies, 2025)
This article examines the position of Shaykh Nawawi al-Bantani in the tradition of hadith studies in the Nusantara by focusing on his biography, educational background, works on hadith, and his role in the development of Islamic scholarship. This study employs a qualitative approach through library research, utilizing the works of Shaykh Nawawi al-Bantani and other relevant scholarly sources. From a biographical perspective, Shaykh Nawawi al-Bantani is recognized as a Nusantara scholar who played a significant role within the Islamic intellectual networks of the nineteenth century. His educational experience in pesantren and in the scholarly circles of Mecca provided a strong foundation for shaping his understanding of hadith. His works demonstrate a consistent use of hadith in discussions of jurisprudence and ethics, following the classical scholarly tradition. Through these writings, his ideas were widely disseminated and became important references in pesantren education. His contribution to hadith studies is evident not only in his scholarly productivity but also in his influence on the formation of hadith teaching traditions in the Nusantara. Therefore, Shaykh Nawawi al-Bantani can be regarded as one of the key figures in the historical development of hadith studies in Indonesia.